Impact of anemia on outcomes and resource utilization in patients with myocardial infarction: A national database analysis - Jhand, Aravdeep S.; Abusnina, Waiel; Tak, Hyo Jung; Ahmed, Arslan; Ismayl, Mahmoud; Altin, S. Elissa; Sherwood, Matthew W.; Alexander, John H.; Rao, Sunil V.; Abbott, J. Dawn; Carson, Jeffrey L.; Goldsweig, Andrew M. (International journal of cardiology, 2024)
Although anemia is common in patients with myocardial infarction (MI), management remains controversial. We quantified the association of anemia with in-hospital outcomes and resource utilization in patients admitted with MI using a large national database. All hospitalizations with a primary diagnosis code for acute MI in the National Inpatient Sample (NIS) between 2014 and 2018 were identified. Among these hospitalizations, patients with anemia were identified using a secondary diagnosis code. Data on demographic and clinical variables were collected. Outcomes of interest included in-hospital adverse events, length of stay (LOS), and total cost. Multivariable logistic regression and generalized linear models were used to evaluate the relationship between anemia and outcomes. Among 1,113,181 MI hospitalizations, 254,816 (22.8%) included concomitant anemia. Anemic patients were older and more likely to be women. After adjustment for demographics and comorbidities, anemia was associated with higher mortality (7.1 vs. 4.3%; odds ratio 1.09; 95% confidence interval [CI] 1.07–1.12, p < 0.001). Anemia was also associated with a mean of 2.71 days longer LOS (average marginal effects [AME] 2.71; 95% CI 2.68–2.73, p < 0.05), and $ 9703 mean higher total costs (AME $9703, 95% CI $9577–$9829, p < 0.05). Anemic patients who received blood transfusions had higher mortality as compared with those who did not (8.2% vs. 7.0, p < 0.001). In MI patients, anemia was associated with higher in-hospital mortality, adverse events, total cost, and length of stay. Transfusion was associated with increased mortality, and its role in MI requires further research. •In a United States administrative claims database including than a million patients with myocardial infarction, those with concomitant anemia had higher mortality, even after adjustment for comorbidities.•Anemia was associated with longer length of stay and greater total costs of myocardial infarction hospitalization.•Anemic patients who received blood transfusions had higher mortality than those who did not receive transfusions.